Strategizing through servitization, Understanding service transition and its outcomes in industrial markets - Luukkainen, Annamari (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
whether the transition towards a service-orientated business can be seen as a successful and beneficial strategy to undertake by industrial manufacturers. This study provides answers on the reasons that trigger industrial manufacturers to transition towards a more servitized business model; which strategic choices are made by industrial manufacturers in the transition towards a more servitized business model, and finally, what the outcomes of servitization look like for industrial manufacturers. Previous research in B2B marketing and service marketing concentrates on the reasons and strategic choices, but little is known on the outcomes, thus this research is filling this gap. This research was carried out as a qualitative study, in which six industrial manufacturers were studied as case companies. The six case companies all belong to the Finnish electricity/electronics/automation industrial segment and include Finnish companies as well as a foreign subsidiary well-established on the Finnish market. A total of 9 interviews with company representatives were carried out using semi-structured interviews; the names of the companies and representatives have been kept confidential. Additional information was gathered from secondary data that included company financial statements, action reports, professional articles and material found on company websites. Findings suggest that industrial manufacturers face pressure mostly from customers and competitors to provide more and more services. In addition to this, services are seen as providing industrial manufacturers with opportunities to improve their market positions, survive in competition and engage in longer lasting relationships with their customers. Industrial manufacturers can create separate service organizations or integrate services into their product units; the integration strategy is seen as being easier and more beneficial. Through servitization, industrial manufacturers can improve their revenues, spread risks, protect themselves against economic uncertainty and finally increase customer satisfaction. However, servitization is challenging, especially in regards to creating the proper mindset and culture, this is especially true for sales teams. Servitization is seen as being a beneficial strategy. Servitization has the potential to the change the industry as a whole and new service growth is expected to stem from digitalization and the use of big data in creating new kinds of services.